Income splitting, settlements and avoidance: taxing the family on business profits - Loutzenhiser, G (2009)
In a progressive income tax system with an individual tax unit, high-rate taxpayers have an incentive to split income with lower-rate family members to minimise the family’s total tax burden. This raises equity and neutrality concerns. Adopting a spousal tax unit limits the gains from income splitting, but the individual is the better choice on privacy, autonomy, equality, definitional, marriage neutrality and work incentive grounds. Once the individual is chosen as the income tax unit, the control model provides a strong policy basis for attributing both earned and unearned income to individuals. Income splitting, however, undermines this model as well as the individual tax unit. This thesis focuses on the UK’s approach to income-splitting in family businesses. The relevant UK income tax rules, particularly the settlements provisions, are inadequate for the task. Various possible reforms are examined. Incorporating a transfer pricing or ‘reasonableness’ test into the settlements provisions would strengthen these rules, but would make taxpayer compliance with an uncertain regime even more difficult. Another option is to expand the scope of employment tax by moving the borderline between employees and the self-employed or companies. Deeper structural reforms could be made to enhance the neutrality of taxation on different legal forms of economic activity. This would reduce the incentives to incorporate for tax savings, including from income splitting. Integration of income tax and NICs is one such option; a dual income tax is another. A TAAR or GAAR also could be pursued. Ultimately, some combination of these various reform options could provide a partial solution to this challenging issue.